Screening common bean germplasm for resistance to genetically diverse Sclerotinia sclerotiorum isolates from Argentina - Aban, Carla Luciana (2020)
White mold caused by Sclerotinia sclerotiorum (Lib.) de Bary is a devastating disease that affects the common bean (Phaseolus vulgaris. L) crop worldwide. In Argentina, white mold has been detected in all bean production areas, reaching seed yield and quality losses up to 100% on susceptible common bean cultivars under favorable weather conditions. The aim of this study was to screen the physiological resistance of 20 common bean accessions to five genetically distinct isolates of S. sclerotiorum collected from the main common bean growing area of Argentina, using the greenhouse straw test. The white mold reaction was scored at 7, 14, and 21 days post-inoculation using a 1 (no disease symptoms) to 9 (severely diseased or dead plants) scale and the area under the disease progress curve (AUDPC) was determined. Highly significant differences (p < 0.001) were observed between isolates, accessions and genotype x isolate interaction at the three evaluations dates. All cultivars and lines were susceptible at the end of the assessment, except line A 195 which was resistant to white mold against the five isolates tested and was significantly different from all accessions. This work represents a valuable contribution to regional breeding programmes aimed to obtain cultivars with durable resistance.